Hubungan Tingkat Konsumsi Madu dengan Pengetahuan Gizi, Status Gizi, dan Kebugaran Remaja di Kota Bogor - A. Septiani; A. Apriantini; T. Suryati (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
Honey consumed regularly is known to improve vitality. The level of vitality can be influenced by several factors, such as the amount of food intake, that related to nutritional knowledge and status. The objectives of this study is to analyze the connection between the knowledge about nutrient, the status of nutrition, and the level of honey consumption to the vitality of adult’s body in Bogor City. Sampling is carried out based on the Slovin formula with a total of 100 respondents and has qualified representatives of adult’s in Bogor City. The status of nutrition measurement by anthropometric method. The data of body vitality level is measured through Balke Test. The data is collected through a questionnaire interview and then descriptively analyzed and tested for the correlation. The results that 69 % of the respondents are lack of knowledge about nutrient. The status of nutrition values is 79 % of them are normal. The highest level of honey consumption is 2 to 3 times a week. The conclusion is the knowledge about nutrient, the status of nutrition, and the level of honey consumption influence the vitality of human body based on the multiple correlation test.